Comparison amid the Service Quality Attributes: Pakistan Hotel Industry Analysis - NASEEB SHAH; PROF. DR. QADAR BAKHSH BALOCH; SOURATH (Journal of Business & Tourism, 2021)
Study focus was to comparatively analyze the expected and actual service quality attributes in the hotel industry of Khyber Pakhtunkhwa, Punjab and Islamabad, Pakistan. Population of the study was comprised of customers/clients of different hotels/ situated at urban areas of Khyber Pakhtunkhwa (KP), Lahore, and Islamabad Capital city of Pakistan. Statistical analysis reveals that there exist significance difference amid the customers/clients of KP, Lahore, and Islamabad Pakistan on expected and actual service quality attributes. The study considered that lodging client’s/customers are the key factor in the friendliness and in up-bring the business prosperity.